Theatricality of the Body in Bode Jatra: A Study of the Tongue-Piercing Culture - Thapa, Hukum (SCHOLARS: Journal of Arts & Humanities, 2023)
The present paper attempts to explore the body in relation to theatricality in Bode Jatra, the tongue-piercing festival of the Newar community in Bode, Bhaktapur. The study treats body as the territorial site to foreground how body performance becomes theatrical, taking the performance of Bode Jatra, the performativity of the tongue-piercing, as its text. The raving performance of tongue piercing generates an expression of cosmogonic consciousness. It encompasses the movement of the body both from micro and macro facet which constitutes the theatrical culmination. Therefore, performativity of the body becomes a trope that necessitates in studying the conception and evolution of theatre with the view that bodily performance is the epitome of theatricality which has hitherto remained veiled. The body which performs liminal in Bode Jatra exerts cosmogonic force that subverts the traditional hierarchy — the mundane world and the world of spirit.